Coherent control over strong-field dissociation of heteronuclear diatomic molecules - Rigsbee, Brandon (Kansas State University, 2015)
In the last 20 years, advancements in laser technology have allowed for the production of intense laser pulses with durations in the femtosecond (10⁻¹⁵ second) regime, giving scientists the ability to probe nuclear dynamics on their natural time scale. Study of the dissociated fragments created by these intense fields can be used to learn about the molecular structure and dynamics. The work presented in this thesis focuses on controlling this light–molecule interaction in such a way that we can preferentially dissociate the molecule to a desired final product. The hydrogen molecular ion, HD⁺, as well as LiF serve as simple systems that can be studied theoretically for a broad range of laser parameters. Our goal in using these relatively simple systems is to capture the essential physics of the light–molecule interaction and develop general methods to describe these interactions in more complex systems.
Keywords: Coherent control; Strong field; Diatomic molecules; Molecular Physics (0609); Physics (0605)